Weaning Difficulty in Patient with End Stage Renal Disease Acute with Respiratory Failure due to Pulmonary Edema and Pneumonia - Bangun, Primta; Suwarman, Suwarman (CoinReads Media Prima, 2023)
Introduction: End Stage Renal Disease (ESRD) 5D patient have potential to respiratory failure due to excess fluid, thus increasing the incidence of repeated hospital admissions. Deaths were reported in about 15%– 30% cases, where 50%–60% of patients needed respiratory support with mechanical ventilation. About 30%– 40% of patients had complications in the weaning process from mechanical ventilation. Prolonged mechanical ventilation increased mortality and morbidity, the length of stay periods and costs. Case Report: This case report will discuss the difficult weaning from mechanical ventilation in patients with ESRD 5D who have respiratory failure due to edema pulmonary and pneumonia who were hospitalized at the Intensive Care Unit (ICU) of Hasan Sadikin Hospital - Bandung for 20 days Conclusion: Weaning difficulty due to accumulation positive fluid balance during hospitalization lead to longer use of mechanical ventilation and pulmonary infection get heavier. A positive cumulative fluid balance could be one factor of weaning difficulty